Is this the end of Public Education in Chile? - Paredes, Ricardo (Estudios de Economía, 2016)
In the period 2000 - 2006, municipal or public schools reduced its enrollment in 186,000 students (13%) in Chile. Meanwhile, privately subsidized schools, receiving the same type of funding, increased their enrollment in 386,000 students (38%). In this paper we distinguish demand factors, associated with parents’ decisions, and supply factors, those associated with owners’ decisions, to explain the change in the education structure en Chile. We found evidence that the asymmetry in the institutional constraints explain only part of the evolution. Other factors, associated with municipal decisions, which in turn are explained by the asymmetric financing of different schools, explain the main part of the change.